Really Truly - Frederick, Heather Vogel (Frederick, Heather Vogel. Pumpkin Falls mystery, 2020)
Truly Lovejoy's hopes for a perfect summer are dashed when she is sent to mermaid academy, complete with a sparkly tail, but she finds a new mystery for the Pumpkin Falls Private Eyes to investigate.